Optimal design of high frequency magnetic links for power conversion used in grid connected solar and wind power plants - Linta Khalil; Kamran Liaquat Bhatti; Kiran Khalil; Haider Bin Tariq; Salman Khalil; Muhammad Zahid Shafique (Energy Reports, 2023)
The high-frequency standard magnetic links were recently considered viable candidates for construction of the medium-voltage power converters, rather than link with the common dc specialized magnetic materials, like nano-crystalline and the amorphous materials. This provides a new route of portable and lightweight incorporation of renewable systems into the direct grid, stepping-up transformer. The main objective is to propose an ideal design approach for magnetic links and to validate their viability by the evaluation of a sample. This will discuss a specific approach to design, research, and implementation. The predicted result is that the proposed architecture strategy will be implemented effectively in the future with clean energy generation schemes and intelligent grids. The current approaches have some critical disadvantages, including voltage mismatch, minimum overall power extraction, and general mode problems because of several direct grid and common dc connections. With emphasis on implementing renewable energies, exploring different forms of configuring structures for efficiency and output is becoming increasingly relevant. Both technologies employ grid-based voltage converters, but conventional equipment poses several problems in terms of voltage balance and maximum power output. Magnetic connections are a viable solution to minimize the costs, reliability, and consistency of the network. Instead of several dc links, these can be solved. Thus, the plan will depend on its optimal design to monitor system costs while improving efficiency by adding a new magnet-powered voltage converter. Particularly the voltage mismatch and typical mode problems of converter systems are minimized. The electromagnetically designed common magnetic links are, however, a multi-physics challenge, affecting device performance and costs. The paper objectives are to propose an ideal design approach for magnetic links and to validate their viability by the evaluation of a sample.